2018
DOI: 10.1038/s41467-018-02882-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of tick-borne encephalitis virus and its neutralization by a monoclonal antibody

Abstract: Tick-borne encephalitis virus (TBEV) causes 13,000 cases of human meningitis and encephalitis annually. However, the structure of the TBEV virion and its interactions with antibodies are unknown. Here, we present cryo-EM structures of the native TBEV virion and its complex with Fab fragments of neutralizing antibody 19/1786. Flavivirus genome delivery depends on membrane fusion that is triggered at low pH. The virion structure indicates that the repulsive interactions of histidine side chains, which become pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
206
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(236 citation statements)
references
References 73 publications
11
206
3
Order By: Relevance
“…Here, we present the crystal structures of LIV E as well as MAb 4.2 scFv in complex with the E protein of either LIV or TBEV. Structural analysis revealed that MAb 4.2 recognizes the lateral ridge of DIII on both E proteins, a hot spot for potent neutralizing antibodies against flaviviruses, as previously reported (6,21,(25)(26)(27)29). Further structural comparison and modeling imply that MAb 4.2 may function by preventing structural rearrangement during the virus-host membrane fusion process.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Here, we present the crystal structures of LIV E as well as MAb 4.2 scFv in complex with the E protein of either LIV or TBEV. Structural analysis revealed that MAb 4.2 recognizes the lateral ridge of DIII on both E proteins, a hot spot for potent neutralizing antibodies against flaviviruses, as previously reported (6,21,(25)(26)(27)29). Further structural comparison and modeling imply that MAb 4.2 may function by preventing structural rearrangement during the virus-host membrane fusion process.…”
supporting
confidence: 63%
“…To date, the crystal structures of several lateral ridge-targeted neutralizing MAbs bound to MBFV E proteins have been reported, as exemplified by E16 for WNV, E106 for DENV1, and ZV67 for ZIKV (25-30, 48, 49). In addition, the cryo-EM structure of the TBEV virion in complex with a lateral ridge-targeting MAb, 19/1786, was recently reported (6). Further comparison reveals that the epitope of MAb 4.2 overlaps these MAbs (Fig.…”
mentioning
confidence: 84%
See 3 more Smart Citations